2022
DOI: 10.2147/ccid.s355260
|View full text |Cite
|
Sign up to set email alerts
|

The Dermoscopic Features of Photoaging and Its Association with Sun Index Score in the Coastal Population at Cilincing, Jakarta: A Cross-Sectional Study

Abstract: Purpose Repeated exposure to ultraviolet light is the most significant factor that contributes to photoaging. Dermoscopy photoaging scale (DPAS) is a noninvasive examination utilized for the diagnosis of photoaging. However, there has been no study analyzing the correlation between DPAS and sun index. Hence, this study aims to find out the dermoscopic features of photoaging and its association with sun index score in the coastal population. Patients and Methods This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…19 type, smoking habits) and sun index scores and found that cheek preference, male, active smoking, Fitzpatrick type IV skin, and increased age had higher DPAS scores. 20 There was no correlation between DPAS scores and the sun index. There were some similarities and overlaps between Hu's and Isik's dermoscopy photoaging evaluation, including linear vessels, branching vessels, and telangiectases; however, there are no studies of the correlation between Hu's and Isik's methods.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…19 type, smoking habits) and sun index scores and found that cheek preference, male, active smoking, Fitzpatrick type IV skin, and increased age had higher DPAS scores. 20 There was no correlation between DPAS scores and the sun index. There were some similarities and overlaps between Hu's and Isik's dermoscopy photoaging evaluation, including linear vessels, branching vessels, and telangiectases; however, there are no studies of the correlation between Hu's and Isik's methods.…”
Section: Discussionmentioning
confidence: 91%
“…Respati et al. correlated DPAS with sociodemographic characteristics (age, sex, skin type, smoking habits) and sun index scores and found that cheek preference, male, active smoking, Fitzpatrick type IV skin, and increased age had higher DPAS scores 20 . There was no correlation between DPAS scores and the sun index.…”
Section: Discussionmentioning
confidence: 99%
“…Being a tropical country with year-round exposure to the sun's ultraviolet rays, Indonesia has a population highly susceptible to photoaging. The prevalence of photoaging symptoms on the face were most commonly found in Javanese ethnicity (30.5%), age group 30-39 years (59.1%), non-smoking behavior (35%), indoor work such as laboratory assistants, employees and teachers (71%), duration of sun exposure > 34 hours/week (62%), Fitzpatrick IV skin type (moderate brown skin) (65%) and lentigo symptoms (28%) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%